The clinical and genetic features in patients coexisting primary breast and thyroid cancers - Fu, Jingyao; He, Miao; Wu, Qiong; Zhang, Xiangkai; Qi, Xin; Shen, Keyu; Wang, Xiaochun; Zhang, Guang (Frontiers in Endocrinology, 2023)
Background We attempted to examine the clinical characteristics in patients with BC and TC; explore the potential mechanisms of tumorigenesis and progression. Methods Using the SEER-9 database, a retrospective study (1975-2017) was conducted on patients with BC and TC. We identified the common differentially expressed genes involved in BC and TC using the Gene Expression Omnibus database (GEO). Immunohistochemical staining was performed to verify the expression of the hit gene in patients with co-occurrence of BC and TC. Using The Cancer Genome Atlas (TCGA) database, the relationship between gene expression and clinicopathological characters was determined. Gene set enrichment analysis (GSEA) was used to identify the pathways enriched in BC and TC. Results BC patients had a higher predisposition to develop TC (SIR 1.29) and vice-versa (SIR 1.12). Most of these patients were differentiated thyroid carcinoma (DTC) and hormone receptor- (HR) positive BC. COMP was significantly overexpressed in BC and TC. COMP was overexpressed in both BC and TC tissues obtained from the same patients validated by IHC. COMP was correlated with worse OS in BC (stage Ⅱ-Ⅳ) and TC; it was the independent factor for prognosis of BC. GSEA indicated that the estrogen response and epithelial-mesenchymal transition (EMT) pathways were significantly enriched in both TC- and BC- COMP overexpression groups. Conclusion The co-occurrence risk of BC and TC in the same individual is higher than in the general population. Overexpression of COMP could promote oncogenesis and progression in patients with BC and TC through estrogen signaling and EMT pathways.